2015
DOI: 10.1002/jbmr.2496
|View full text |Cite
|
Sign up to set email alerts
|

Co-administration of Antiresorptive and Anabolic Agents: A Missed Opportunity

Abstract: Co-administration of antiresorptive and anabolic therapies has appeal because these treatments target the two main abnormalities in bone remodeling responsible for bone loss and microstructural deterioration. Antiresorptives reduce the number of basic multicellular units (BMUs) remodeling bone and reduce the volume of bone each BMU resorbs. Intermittent parathyroid hormone (PTH) increases the volume of bone formed by existing BMUs and those generated by PTH administration. PTH also increases bone formation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 84 publications
(174 reference statements)
0
43
0
Order By: Relevance
“…The rapid increase in cortical porosity and decrease in trabecular BV/TV are the net result of many excavated sites that appear at the same time as refilling occurs in the fewer cavities excavated pre-lactation, before remodeling becomes rapid. (35) The fewer sites excavated pre-lactation do not refill immediately. Refilling is delayed by the reversal phase, and then proceeds slowly, during 3 months, and so occurs during early lactation when rapid remodeling begins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid increase in cortical porosity and decrease in trabecular BV/TV are the net result of many excavated sites that appear at the same time as refilling occurs in the fewer cavities excavated pre-lactation, before remodeling becomes rapid. (35) The fewer sites excavated pre-lactation do not refill immediately. Refilling is delayed by the reversal phase, and then proceeds slowly, during 3 months, and so occurs during early lactation when rapid remodeling begins.…”
Section: Discussionmentioning
confidence: 99%
“…Refilling is delayed by the reversal phase, and then proceeds slowly, during 3 months, and so occurs during early lactation when rapid remodeling begins. (35) This delay in the initiation and slowness of the refilling phase produces a transient deficit in bone matrix and mineral. (36) If rapid remodeling was the only abnormality associated with estrogen deficiency, the increase in cortical porosity and decrease in trabecular density produced would be expected to be fully reversed because all the cavities excavated producing the transient deficit in bone matrix and mineral eventually fully reverse with cessation of lactation and restoration of estrogen production.…”
Section: Discussionmentioning
confidence: 99%
“…(13,14) The delay in resorption marker increase after starting PTH treatment can be explained by the principles of basic multicellular unit (BMU)-based remodeling. (15)(16)(17)(18) BMUs remodeling bone are in their resorptive, reversal, or formative phases. At any time, there are more BMUs in their formation phase at various locations than there are BMUs in their resorption phase at other locations (because the duration of the formation phase is longer than the resorption phase).…”
Section: Anabolic Therapy With Parathyroid Hormone (Pth) and Abaloparmentioning
confidence: 99%
“…(43,44) As discussed below and elsewhere, resorption and formation "markers" are not accurate surrogates of volumes of bone matrix resorbed or formed. (18,45) Whether PTHrP(1-36) and teriparatide produce a similar anabolic effect but PTHrP(1-36) produces less bone resorption than teriparatide was not evaluated; no histomorphometry was performed. However, a recent large study of iliac crest biopsies from the Miller and colleagues study (1) reported no differences in static or dynamic indices of bone formation or resorption between the two drugs.…”
Section: Anabolic Therapy With Parathyroid Hormone (Pth) and Abaloparmentioning
confidence: 99%
See 1 more Smart Citation